Answer:
2,-1
Step-by-step explanation:
2x^2 -2x -4 =0
Factor out a 2
2(x^2 -x-2) =0
What 2 number multiply to -2 and add to -1
-2*1 = -2
-2 +1 = -1
2(x-2) (x+1) =0
Using the zero product property
x-2 = 0 x+1 = 0
x-2+2=0+2 x+1-1=0-1
x=2 x=-1
Answer: I think this is right
Step-by-step explanation:
All but B, as on B an a can be factored out
Answer:
E. 35°, 70°
Step-by-step explanation:
Sum of angles add up to 180° in every triangle.
Step 1: Set up equation
a + 2a + 75 = 180
Step 2: Combine like terms
3a + 75 = 180
Step 3: Subtract 75 on both sides
3a = 105
Step 4: Divide both sides by 3
a = 35
So 1 angle is 35°
Step 5: Plug in <em>a</em> to find last angle
2(35) = 70°
Answer:
xtcygvubhjnlkm;lbu
Step-by-step explanation: